One-pot synthesis of layered zeolites
Through direct hydrothermal synthesis and high shear mixing treatment, combined with dual organic additives of CTA+ and OSDA, high-layer Al-SSZ-70 zeolite was successfully prepared, solving the synthesis difficulty and cost problems in the existing technology and achieving high catalysis Improved performance and structural integrity.
Patent Information
- Application Number
- CN202380042151.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-23
- Filing Date
- 2023-05-23
- Publication Date
- 2025-01-03
AI Technical Summary
The prior art is difficult to effectively synthesize highly layered MWW type zeolites under mild conditions, especially while maintaining structural integrity and avoiding dissolution of amorphous silica, and there are scale and cost problems.
Direct hydrothermal synthesis method combined with CTA+ (hexadecyltrimethylammonium) cation and OSDA (imidazolium cation) as dual organic additives, and high shear mixing treatment was performed after synthesis to prepare a layer of high silica Al-SSZ-70 zeolite.
A stratified MWW zeolite with high surface area (at least 340 m2/g) and a small amount of amorphous phases is achieved, which extends the range of Si/Al ratio, improves catalytic performance, and reduces synthesis costs.
Smart Images

Figure CN119255866A_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority to U.S. Provisional Application No. 63 / 344,806, filed May 23, 2022, the entire disclosure of which is incorporated herein by reference in its entirety. This invention was made with support from the U.S. Government under U.S. Department of Energy DE-FG02-05ER15696. The U.S. Government has certain rights in this invention. Technical Field
[0003] The present invention relates to the synthesis of delaminated layered materials which can be used in reactions involving sterically bulky reactants. The synthesis is a direct "one-pot" synthesis. Background Art
[0004] Zeolite is a microporous material composed of aluminosilicate TO4 tetrahedrons, which has a unique crystal structure composed of molecular channels and holes. Although zeolite has been applied to many fields (such as catalysis, gas separation and adsorption) because of its unique three-dimensional restriction controlled by microporosity, their application is mainly limited to those molecules that are sufficiently small to freely enter these internal voids. Spatially bulky molecules are often subject to strict diffusion constraints because their macromolecular size prevents them from entering the microporous channels of zeolite. Therefore, for expanding the catalog repertoire of zeolite to include spatially bulky molecules, various methods have been developed to introduce hierarchical porosity into conventional microporous zeolites, including soft / hard templates, demetallization, etc.
[0005] In particular, the synthesis of hierarchical zeolites by delamination of two-dimensional (2D) layered zeolite precursors has attracted great attention. Part of this effort has been stimulated by the recent demonstration of partial confinement on the outer surface pockets of 2D MWW-type zeolite layers, which accelerates catalytic reactions in both gas and liquid phases. In 1998, Corma and co-workers have pioneered the synthesis of 2D MWW-type zeolite layers via post-synthesis delamination of layered zeolite precursors, where a zeolite with a mass of about 700 m was synthesized. 2 / g of external surface area of ITQ-2 zeolite. However, due to the high pH and elevated temperature of the post-treatment conditions involved in the delamination, an undesirable consequence can be dissolution of silica and amorphization of the zeolite. For this reason, in subsequent work, every effort has been made to increase the mildness of the delamination conditions in order to maintain the structural intra-layer integrity of the delamination zeolite and avoid the reduction of the Si / Al ratio associated with the dissolution of the framework silica. In this regard, the synthesis of UCB-3 zeolite with delaminated MWW layers under mild conditions was reported, but it required the use of corrosive halide reagents including fluoride and sonication, which were also required in all variants of the delamination zeolites reported previously. Difficulties in scale-up were encountered.
[0006] However, as opposed to post-treatment methods, direct synthesis of the layered MWW zeolites by hydrothermal synthesis is more desirable but also highly challenging. Although recent studies have shown that both MIT-1 and DS-ITQ-2 zeolites composed of layered MWW layers can be prepared during direct hydrothermal synthesis processes, the requirement to use a diquaternary ammonium (diquat)-organic structure directing agent (OSDA) can be limiting from a practical point of view. DS-ITQ-2 is reported to consist of 70% of single and double MWW layers and has a molecular weight of about 300 m / s. 2 / g of surface area, which is less than half the surface area reported for ITQ-2. Recently, Rimer and co-workers demonstrated that the combination of OSDA containing hexamethyleneimine (HMI) and the simple surfactant cetyltrimethylammonium bromide (CTAB) produced layered MCM-22 zeolites in a direct synthesis. However, to avoid the synthesis of an amorphous phase when using this method, a narrow window of Si / Al ratio is required, which is limited to a range of low Si / Al values that is less desirable for catalysis. In addition, these reports omitted key PXRD data at low angles of about 5 degrees 2θ and lower. These data are needed to assess the presence of a reticular, mesoporous, amorphous silica phase. The possible existence of such a phase remains an important fundamental question because, by its very nature, the synthesis of layered zeolites requires the retention of two-dimensional order within the zeolite nanosheets and the destruction of three-dimensional order between the nanosheets, thereby separating these nanosheets in a house-of-cards arrangement. The ongoing nature of this challenge can be summarized by the following typical question: What is the selective synthesis method for maintaining order within the nanosheets while breaking the bonds between nanosheets, all while avoiding the presence of an amorphous phase? It is not trivial to further raise this question by requiring an eco-friendly (no halide reagents), scalable (no sonication), and practical from a cost perspective (synthesis without expensive surfactants).
[0007] Thus, despite significant progress in synthesizing near-monolithic MWW materials, existing synthesis experiments have highlighted the difficulty of synthesizing hierarchical MWW zeolites with a highly hierarchical architecture, particularly while minimizing the presence of an amorphous phase, given the above constraints. It would be highly desirable to extend the synthesis of monolithic MWW materials to a wider span of Si / Al compositions, particularly relatively high framework Si / Al ratios, as required in catalysis. Summary of the invention
[0008] A method is provided which combines direct hydrothermal synthesis with CTA +(hexadecyltrimethylammonium) cations and OSDA (in one embodiment, and post-synthesis high shear mixing treatment). This method synthesizes highly layered Al-SSZ-70 zeolites. The zeolite can exhibit at least 340 m 2 / g (e.g. 347m 2 The presence of dual organic additives in the hydrothermal synthesis is believed to effectively inhibit the stacking of the MWW layers by capping the outer surfaces of the MWW layers with surfactants. This unique synthesis method synthesizes high silica layered MWW zeolites with little or no amorphous phase, which was previously impossible by using CTA-based + The direct synthesis of simple cationic surfactants has not been achieved. In one embodiment, based on the total organic components (OSDA + CTA + ) + The mole % is in the range of 10 to 60 mole %. In one embodiment, the Al-SSZ-70 zeolite has a Si / Al ratio of at least 50.
[0009] Among other factors, a new synthetic route is provided, which generates a high-silica layered MWW-type zeolite Al-SSZ-70. Some benefits are also achieved by post-synthesis high shear mixing of the layered zeolite precursor (to affect further layering). The resulting layered zeolite shows similar Brønsted / Lewis acid site distribution (characterized by FTIR spectra of pyridine adsorption at different temperatures) and enhanced acid catalytic performance over non-layered zeolites. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] Figure 1A Shown are the PXRD patterns of as-synthesized layered Al-SSZ-70 zeolites synthesized with different molar amounts of CTAOH in the synthesis gel, as indicated by percentage. Figure 1B Shown are the PXRD patterns of the present layered Al-SSZ-70 zeolites which have been direct calcined but synthesized with different molar amounts of CTAOH in the synthesis gel, as indicated by percentage. Figure 1C Shown are the PXRD patterns of the as-synthesized Al-SSZ-70 zeolite after high shear mixing treatment, the samples being synthesized with different molar amounts of CTAOH in the synthesis gel, as indicated by percentage.
[0011] Figure 2A -D shows the N2 physisorption isotherm for a straight-calcined and high-shear mixed Al-SSZ-70 zeolite with 10 mol% CTAOH ( Figure 2A )、30 mol% CTAOH( Figure 2B )、50 mol% CTAOH( Figure 2C) and 60 mol% CTAOH ( Figure 2D ).
[0012] Figure 3A Figure 2 shows the OSDA and CTA in the as-synthesized sample. + The weight percentage and Figure 3B Figure 2 shows the OSDA and CTA in the as-synthesized sample. + The as-synthesized samples were synthesized with different molar amounts of CTAOH.
[0013] Figure 4A -H shows the SEM images of the corresponding samples of calcined Al-SSZ-70 zeolite after high shear mixing. The zeolite was treated with 10 mol% CTAOH ( Figure 4A )、30 mol% CTAOH( Figure 4C )、50 mol% CTAOH( Figure 4E ) and 60 mol% CTAOH ( Figure 4G ) hydrothermally synthesized, the corresponding sample was prepared for 10 mol% CTAOH ( Figure 4B )、30 mol% CTAOH( Figure 4D )、50 mol% CTAOH( Figure 4F ) and 60 mol% CTAOH ( Figure 4H ).
[0014] Figure 5A -H shows Al-SSZ-70 (0%) zeolite ( Figure 5A and 5B )、Al-SSZ-70(0%)-HSM zeolite( Figure 5C -D) and Al-SSZ-70(60%)-HSM zeolite ( Figure 5E -F) TEM image.
[0015] Figure 6 Shown are C-NMR spectra of Al-SSZ-70 zeolites synthesized with 0 mol % CTAOH, 50 mol % CTAOH, and 60 mol % CTAOH.
[0016] Fig. 7A and 7B shows the transmission FTIR spectrum of pyridine at 423K ( Fig. 7A ) and 523K( Figure 7B ) in (H)Al-SSZ-70(0%), (H)Al-SSZ-70(0%)-HSM and (H)Al-SSZ-70(60%)-HSM. The spectrum is at 1740-2080 cm -1 The range is normalized to Si-O-Si harmonics. DETAILED DESCRIPTION
[0017] The present method allows the preparation of a layered Al-SSZ-70 zeolite. The method comprises contacting a reaction mixture comprising (1) an Al2O3 source; (2) a silica source; (3) an imidazolium cation (OSDA); and (4) a hexadecyltrimethylammonium cation (CTA) under crystallization conditions. + In one embodiment, the reaction mixture further comprises (5) Al-SSZ-70 zeolite seeds. Preferably, the Al-SSZ-70 seeds have a Si / Al ratio of at least 50. The term Si / Al (silicon dioxide to aluminum ratio) refers to the molar ratio of silicon oxide (SiO2) to aluminum oxide (Al2O3).
[0018] Based on total organic fraction (OSDA+CTA + ) + The mole % of CTA is generally in the range of 10 mol % to 60 mol %. This is important. In another embodiment, CTA + In another embodiment, the amount of CTA is in the range of 10 mol% to 50 mol%. + In the range of 30 mol % to 60 mol %, or even in the range of 50 mol % to 60 mol %. When combined with any suitable anion, the CTA can provide + The CTA is preferably provided in the reaction mixture in the form of CTAOH. + .
[0019] In the preparation of SSZ-70, an imidazolium cation, which is selected from 1,3-diisopropylimidazolium cation, 1,3-diisobutylimidazolium cation and 1,3-dicyclohexylimidazolium cation, is used as a structure directing agent ("OSDA"), also known as a crystallization template. The OSDA that can be used to prepare SSZ-70 is represented by the following structures (1), (2) and (3):
[0020]
[0021] The OSDA cation is typically associated with an anion, which may be any anion that is not detrimental to the formation of the zeolite. Representative anions include elements from Group 17 of the periodic table (e.g., fluoride, chloride, bromide, and iodide), acetate, carboxylate, hydroxide, sulfate, and the like.
[0022] The alumina source may include a FAU framework zeolite. The FAU framework type zeolite may be an ammonium zeolite or a hydrogen zeolite. Examples of the FAU framework type zeolite include zeolite Y (e.g., CBV720, CBV760, CBV780, HSZ-HUA385, and HSZ-HUA390). Zeolite Y may have a SiO2 / Al2O3 molar ratio of 30-500. The FAU framework type zeolite may include two or more zeolites. The two or more zeolites may be Y zeolites with different silica to alumina molar ratios. The FAU framework type zeolite may be the sole or primary source of silicon and aluminum. Another suitable source of aluminum oxide may be sodium aluminate.
[0023] Individual sources of silicon include colloidal silica, fumed silica, precipitated silica, alkali metal silicates and tetraalkylorthosilicates.
[0024] Crystallization of SSZ-121 molecular sieve from the above reaction mixture can be carried out in a suitable reactor vessel (e.g., a polypropylene tank or a Teflon-lined or stainless steel autoclave) under static, tumbling or stirring conditions, at a temperature of 100-200° C. (e.g., 150-175° C.) for a sufficiently long time (e.g., 1-14 days or 2-10 days) to allow crystallization to occur at the temperature used. The hydrothermal crystallization method is usually carried out under pressure (e.g., in an autoclave), and is preferably carried out under autogenous pressure.
[0025] Once the molecular sieve crystals are formed, the solid product can be recovered from the reaction mixture by standard mechanical separation techniques (such as centrifugation or filtration). The recovered crystals are washed with water and then dried to obtain molecular sieve crystals in a synthetic state. The drying step can be carried out at an elevated temperature (e.g., 75° C. to 150° C.) for several hours (e.g., about 4 to 24 hours). The drying step can be carried out under vacuum or at atmospheric pressure.
[0026] Once crystallized, the delaminated Al-SSZ-70 zeolite is recovered. The zeolite may be calcined or treated with ozone to remove OSDA. The recovered zeolite may exhibit a Si / Al ratio of at least 50, and in one embodiment, the Si / Al ratio is 50-75.
[0027] In one embodiment, the layered Al-SSZ-70 zeolite of described recovery is also recovered and is subjected to high shear mixing.This can be carried out before calcining.This high shear mixing can comprise the high shear treatment of at least 1500RPM that continues at least 1 minute.In one embodiment, this high shear mixing comprises the high shear treatment of at least 1500-3000RPM that continues in the time period within the scope of 1 minute-30 minutes.In another embodiment, this high shear mixing comprises the high shear treatment of at least 2500RPM that continues at least 2 minutes, is followed by the second high shear treatment of at least 1700RPM that continues at least 1 minute.
[0028] It has been found that the use of high shear mixing provides additional stratification and increased surface area. In one embodiment, the recovered product may exhibit at least 250 m 2 In another embodiment, the product zeolite recovered after high shear mixing is at least 300 m 2 / g, or even 340m 2 / g or greater. The product may also exhibit a value greater than 0.1cm 3 / g of micropore volume, indicating a significant crystalline structure.
[0029] In the following discussion and examples, a Cu Kα radiation source ( Powder X-ray diffraction patterns (PXRD) were collected using a Rigaku Ultima IV diffractometer at 35 kV, 25 mA). SEM images were captured using a Hitachi S5000 microscope. High-resolution transmission electron microscopy (HRTEM) images were captured in low-dose mode using a JEOL JEM 2010 microscope, which was operated at 200 kV accelerating voltage and equipped with a LaB6 electron gun. The samples were prepared by embedding and curing in epoxy resin and then cutting thin sections (~30-50 nm) with a Leica EMUC7 ultramicrotome. The sections were floated on a 300 mesh Cu grid with a thin (20-30 nm) lace-like carbon support film. Images were captured using a Gatan OneView 4k×4k camera. N2 adsorption isotherms at 77 K were measured on a Micromer it ics ASAP2020 adsorption instrument. Solid-state spectroscopy was recorded on a Bruker DSX500 spectrometer and a Bruker 4 mm MAS probe under Bloch decay and cross-polarization MAS conditions. 13 C MAS NMR spectroscopy. Thermogravimetric analysis (TG) was performed on a TA Instruments 2950 thermogravimetric analyzer.
[0030] More specifically, the present synthesis employed molar ratios of CTAOH to OSDA in the reaction mixture ranging from 1:9 to 6:4. The importance of this can be seen when performing a "one-pot" synthesis of layered Al-SSZ-70 zeolites using different CTAOH to OSDA ratios, while keeping the total organic hydroxide content fixed. The PXRD patterns of the corresponding as-synthesized samples are shown in Figure 1A The samples were prepared in Examples 1 to 3. The synthesis conditions are listed in Table 4 below.
[0031] The samples composed of 10-50 mol% CTAOH in the total organic hydroxides (total defined as the number of moles of CTAOH+OSDA) exhibited the characteristic PXRD pattern of Al-SSZ-70 zeolite. The obtained as-synthesized zeolite with 10 mol% CTAOH exhibited a more distinguishable PXRD pattern, indicating that it has a highly crystalline MWW-type structure. When the content of surfactant CTAOH was further increased to 60 mol% CTAOH in the total organic hydroxides, as shown in FIG. Figure 1A As shown in Figure 2, a zeolite product with a much weaker MWW structure PXRD intensity was obtained, suggesting a profound effect of CTAOH on the zeolite crystal growth. Figure 1A In the 50 mol % and 60 mol % CTAOH samples shown in , a small amount of additional phase was observed in the as-synthesized zeolite product, indicated by the appearance of a small PXRD peak at about 5 degrees. This appears to be attributed to the small amount of mesoporous amorphous silica phase in both materials. The crystalline Al-SSZ-70 zeolite is dominant over the amorphous phase in the product, as the (310) reflection at 2θ values of 26-27 degrees is still distinguishable. This indicates long-range ordering of the crystalline MWW layers. At even higher levels of CTAOH surfactant (70 mol %-90 mol % in the synthetic gels), except for the Figure 1A The MFI impurity phase is present in the as-synthesized product shown, and a mixed phase is also observed, which has a higher proportion of amorphous silica. This result indicates that with less OSDA (i.e., diisobutylimidazolium hydroxide), CTA + The surfactant plays a major role in directing the formation of the amorphous silicate material as well as the additional minor impurity phase consisting of the MFI-type zeolite. Therefore, the above data indicate that the amount of CTAOH surfactant should be carefully controlled in the range of 10 mol% to 60 mol% for a cleaner synthesis of the desired delaminated SSZ-70 zeolite as the major phase. The PXRD pattern of the calcined sample is shown in Figure 1B and exhibited a well-resolved PXRD pattern corresponding to Al-SSZ-70 zeolite.
[0032] In addition to direct calcination, high shear mixing of the as-synthesized Al-SSZ-70 zeolite was also employed. This affected further demixing. The PXRD patterns of these high shear mixed samples after their calcination are shown in Figure 1C and showed Figure 1C A similar PXRD pattern is shown for the corresponding straight-calcined Al-SSZ-70 zeolitic material (without high shear mixing). This result indicates that the crystal structure remains intact without significant degradation during the high shear mixing process.
[0033] In addition to the crystal structure, the porosity of the obtained zeolite samples is also of interest. The N2 physical adsorption isotherms of the corresponding directly calcined zeolite products (using 10 mol%, 30 mol%, 50 mol% and 60 mol% CTAOH during the hydrothermal synthesis) are shown in Figure 2A When considering the synthesis of Al-SSZ-70 zeolite seeds without CTAOH (used in an amount of 5 wt% in each zeolite synthesis), the control Al-SSZ-70 (0%) of the direct calcined zeolite has a molecular weight of 161 m 2 The surface area of the calcined zeolite is 117 m / g, as shown in Table 2. This is comparable to the surface area of several MWW-type zeolite materials in the literature, which undergo a certain degree of demixing during the synthesis process. In the case of using 10 mol% CTAOH in the synthesis (synthesis conditions are entry 1 of Table 4 in Example 2), the surface area of the calcined zeolite is 117 m / g. 2 / g (Table 1 below, Al-SSZ-70 (10%)), indicating that a small amount of CTAOH surfactant does not increase the degree of stratification of the MWW zeolite layers during synthesis, and may actually slightly reduce the degree of stratification of the MWW zeolite layers. Figure 1B The high resolution PXRD pattern shown is consistent.
[0034] However, as the CTAOH mole fraction in the synthesis gel increases above 30 mol %, the external surface area of the straight-calcined zeolite becomes significantly higher in Table 1, consistent with an increased degree of stratification. It should be noted that with 50 mol % or 60 mol % CTAOH in the synthesis gel, the external surface area of the corresponding straight-calcined Al-SSZ-70 zeolite in Table 1 below is 257 m 2 / g or 301m 2 / g. These values are significantly higher than those previously reported for layered Al-SSZ-70 zeolite. They are close to and equal to the surface area of di-quaternary ammonium layered DS-ITQ-2 previously reported. Therefore, the physical adsorption results indicate that the surfactant CTA +Partial substitution of OSDA facilitates the delamination of MWW layers during the hydrothermal synthesis. In addition to the external surface area, the mesopore volume also increases with increasing the amount of CTAOH in the synthesis gel from 10 mol% to 60 mol%, while both the micropore surface area and micropore volume decrease accordingly. For example, based on the data in Table 1, in the case of using 60 mol% CTAOH, the directly calcined zeolite has a surface area of 0.107 cm 3 The low micropore volume of 2.5 cm / g is significantly lower than the 0.134 cm / g of Al-SSZ-70 synthesized without CTAOH surfactant. 3 This further supports the delamination of MWW layers with the help of CTAOH surfactant. It should be noted that the increased surface area and mesopore volume cannot be caused by the formation of an amorphous mesoporous phase, which is caused by Figure 1C The PXRD data show that because the 3 The micropore volume of g still indicates a high percentage of crystalline microporous phase.
[0035] The effect of the high shear mixing treatment prior to calcination was demonstrated for the as-synthesized Al-SSZ-70 zeolites without CTAOH and for those materials synthesized with 10 mol% to 60 mol% CTAOH in the synthesis gel. + Based on the N2 physisorption results, for the Al-SSZ-70 zeolite using 0 mol% CTAOH, the 146 m in Table 1 was 2.3 wt% after high shear mixing compared to the directly calcined analog. 2 / g surface area is slightly reduced (compared to 161m 2 / g, Table 1). This indicates that in the absence of CTAOH, this as-synthesized method itself is ineffective for delamination of the MWW zeolite layers. On the other hand, for the as-synthesized Al-SSZ-70 zeolites with 10 mol% to 60 mol% of the surfactant CTAOH, the surface area increased after high shear mixing compared to the corresponding directly calcined samples in Table 1. The Al-SSZ-70 zeolite synthesized with 60 mol% CTAOH showed an increase in surface area of 347 m / s after high shear mixing. 2 g -1 The surface area (compared to the 301m 2 g -1The increase in the surface area of the Al-SSZ-70 zeolite in the synthesized state after high shear mixing emphasizes the unique characteristics of this synthetic route. The presence of the surfactant CTAOH in the hydrothermal synthesis is not only conducive to direct stratification during the hydrothermal synthesis to form a hierarchical porous system, but it is also conducive to the formation of a higher degree of stratification via post-synthesis high shear mixing. Therefore, the present method using the surfactant CTAOH and OSDA as dual organic additives during the synthesis of Al-SSZ-70 zeolite demonstrates the possibility of constructing a hierarchical MWW zeolite with a highly stratified structure and a high framework Si / Al composition of 50 by using this combined method.
[0036] Table 1: Physical adsorption data of Al-SSZ-70 zeolite synthesized with different amounts of CTAOH and after high shear mixing (HSM)
[0037]
[0038] a The data listed in Table 1 were calculated based on the N2 physical adsorption isotherm at 77 K.
[0039] b SA: surface area.
[0040] c PV: pore volume.
[0041] The combination of TGA and CHN analysis data also confirmed that OSDA was partially replaced by the surfactant CTAOH. Figure 3A As shown in Figures 1 and 2, increasing the CTAOH content in the synthesis gel leads to a corresponding increase in the surfactant content in the as-synthesized zeolite product. For example, it was found that the CTAOH content in the as-synthesized zeolite products of Al-SSZ-70 (50%) and Al-SSZ-70 (60%) was + The weight percentage is in the range of 30 wt% to 35 wt%, and the CTA calculated in the final synthesized zeolite + The corresponding mole percentage of OSDA is about 70 mol% to 80 mol%. The effect of this replacement of OSDA by CTAOH surfactant in the as-synthesized Al-SSZ-70 zeolite sample is similar to that of CTAOH during the synthesis process. + The increase in surface area observed with increasing amounts of surfactant is consistent. This result supports the hypothesis that the presence of large amounts of surfactant favors the formation of highly stratified Al-SSZ-70 zeolite during the hydrothermal synthesis.
[0042] exist Figure 4AIn Figures 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30 ... Figure 4G After high shear mixing treatment, the corresponding zeolites showed similar morphology to their directly calcined analogs, but the crystal particles were further broken into smaller fragments ( Figure 4B , 4D , 4F and 4H), which is consistent with the expectation of further zeolite demixing.
[0043] To better understand the combined effects of post-synthesis high shear mixing and hydrothermal synthesis involving CTAOH, Al-SSZ-70 zeolites synthesized with 0 mol% and 60 mol% CTAOH after high shear mixing were examined by TEM imaging. Images of the latter samples are shown in Figure 5E and 5F These data confirm that most of the individual MWW layers are fully delaminated and disordered. Most of these individual MWW layers are curved, which is similar to the morphology observed by SEM and consistent with the delaminated layers. Figure 5A and 5B In contrast to those shown in , which shows a control Al-SSZ-70 zeolite with 0 mol % CTAOH in the synthesis gel after high shear mixing, it exhibits a bulk crystalline morphology consisting of multiple MWW layers.
[0044] exist Figure 5G and 5H In the above Figure 5E and 5F Some reticular mesoporous amorphous phase was observed in the same layered material shown (i.e., Al-SSZ-70(60%)-HSM). This indicates that high levels of surfactant (e.g., 60 mol% CTAOH substitution level for OSDA) also induce the formation of a small amount of amorphous aluminosilicate phase during the hydrothermal synthesis. Figure 1A For the as-synthesized material with 60 mol% CTAOH in the amorphous phase, it is believed that the amorphous phase is responsible for the minor PXRD peak at about 5 degrees 2θ. This attribution is consistent with the PXRD reflections at about 5 degrees 2θ observed previously in amorphous mesoporous materials. The presence of this minor peak cannot be attributed to the swollen MWW layer in the precursor because no such swollen MWW layer was observed by TEM imaging.
[0045] use 13Comparison of C MAS NMR spectra The possible presence of an amorphous phase in the Al-SSZ-70 zeolite samples synthesized with 60 mol% CTAOH in the synthesis gel and the Al-SSZ-70 materials synthesized with lower CTAOH substitution levels of 10 and 50 mol% CTAOH is of interest. The Al-SSZ-70 with 10 mol% CTAOH exhibits the same amorphous phase as that observed with OSDA and CTA. + The NMR resonance caused by the two cations is shown in Figure 6 In. By Figure 3A and CHN analysis data in B, OSDA and CTA + The coexistence of cations is consistent with the organic composition of the as-synthesized zeolite. However, at 50 mol% and 60 mol% high CTA + The NMR spectra of the obtained zeolite showed the same trend for CTA. + Two different environments for cations. One environment corresponds to Figure 6 The resonance around 14.5-15 ppm in the zeolite spectrum represents the characteristic sharp resonance of Al-SSZ-70 zeolite synthesized with 10 mol% CTAOH. In addition, a shoulder peak around 15 ppm was observed for Al-SSZ-70 zeolite synthesized with 50 mol% and 60 mol% CTAOH, which is attributed to the CTA + The same head group of the cation, but in a more restricted and less mobile environment where it is part of a confined surfactant ensemble. For the Al-SSZ-70 zeolite with 60 mol% CTAOH, an enhanced signal intensity of the resonance at 15 ppm was observed compared to the zeolite synthesized with 50 mol% CTAOH. For the Al-SSZ-70 zeolite with 60 mol% CTAOH, which is templated by the surfactant ensemble, the presence of an amorphous phase observed via TEM could be responsible for the appearance of the NMR shoulder at 15 ppm, which is consistent with the CTA being confined in the mesoporous channels. + Therefore, the above results indicate that the use of 60 mol% CTAOH may have led to the formation of a small amount of amorphous phase in the final product.
[0046] The above results highlight the ongoing challenge of disrupting order in the precursor in the z direction (i.e., along the c-axis) without synthesizing an amorphous phase. The CTAOH substitution levels used in the present method for synthesizing Al-SSZ-70 were in the range of 50 mol% to 60 mol% with minimal amorphous phase.
[0047] Also of interest is the distribution of acid sites in the layered Al-SSZ-70 prepared by the present method. The (H)Al-SSZ-70 (60%)-HSM catalyst as well as two Al-SSZ-70 controls synthesized in the absence of CTA surfactant, both with and without high shear mixing ((H)Al-SSZ-70 (0%) and (H)Al-SSZ-70 (0%)-HSM) were studied using pyridine as a relevant probe. This procedure is described in Example 4 below.
[0048] The data shown in Table 2 indicate that all three catalysts have the same total number of acid sites, as detected gravimetrically via pyridine adsorption at a temperature of 423 K, which is about 290 μmol / g. For (H)Al-SSZ-70 (0%), the pyridine total acid site counts in Table 2 are the same as those previously reported for Al-SSZ-70. The delamination process, including the high shear mixing treatment, does not change the number density of total acid sites within the zeolite. In terms of the distribution of acid sites, Fig. 7A The data in B and B generally prove that the Lewis (1454 cm -1 ), Bronstead (1544cm -1 ) and weakly physiologically adsorbed pyridine (1445 cm -1 These data show that for the delaminated (H)Al-SSZ-70(60%)-HSM sample as well as the control Al-SSZ-70 material (which was not exposed to CTA in the presence of + Similar normalized L / B (Lewis to Bronsted ratio) band area ratios were observed for both samples. + Neither substitution of OSDA by surfactant alters these ratios (or equivalently changes the distribution of acid sites) in any significant way.
[0049] Table 2: The Lewis (L, 1449 cm) values corresponding to various desorption temperatures are listed at the top of the table. -1 ) and Brønsted (B, 1544cm -1 ) Calculated integrated band areas of acid sites. All spectra were acquired at 323 K under vacuum after treatment in Ar (50 mL / min) for 1 h at the indicated desorption temperature.
[0050]
[0051]
[0052] The Friedel-Crafts acylation of 2-methoxynaphthalene (2-MN) with acetic anhydride was also investigated as a related probe reaction, and the run details are given below in Example 5. The delaminated (H)Al-SSZ-70(60%)-HSM was compared with two other calcined control catalysts, which were prepared from Fig. 7A and B and the same two materials studied in Table 2 above ((H)Al-SSZ-70(0%) and (H)Al-SSZ-70(0%)-HSM). The data shown in Table 3 below summarizes the results. For all catalysts, the main product observed (>90%) was 1-acetyl-2-methoxynaphthalene (1,2-AMN), consistent with previous work. Due to the harsh reaction conditions (120°C and lack of strict anhydrous conditions), significant coking (the catalyst used was black) and lack of complete material balance closure during catalysis were observed. Nevertheless, the data shown in Table 4 demonstrate that the two control catalysts have the same 1,2-AMN product formation rate, leading to the conclusion that high shear mixing itself is ineffective for increasing the availability of external acid sites. In contrast, the sample with the largest amount of external surface area, i.e., the layered Al-SSZ-70 with 60% CTAOH in the synthesis gel, has a 1.7-fold higher productivity of 1,2-AMN product. In addition, the catalyst has a 2-MN reaction rate 1.2 times higher than any of the controls. This layered Al-SSZ-70 with 60% CTAOH in the synthesis gel is an excellent catalyst with enhanced catalytic performance related to the increased external surface area and availability of external acid sites.
[0053] Table 3: Catalytic results of the Friedel-Crafts acylation of 2-methoxynaphthalene (2-MN) using acetic anhydride as the acylating agent
[0054]
[0055]
[0056] 2-MN: 2-methoxynaphthalene; 1,2-AMN: 1-acetyl-2-methoxynaphthalene; 2,6-AMN: 2-acetyl-6-methoxynaphthalene; 2,8-AMN: 2-acetyl-8-methoxynaphthalene.
[0057] The following examples are offered by way of illustration only and are not meant to be limiting.
[0058] Example
[0059] Example 1
[0060] Synthesis of conventional Al-SSZ-70 zeolite with Si / Al ratio of 50
[0061] A conventional microporous zeolite Al-SSZ-70 with Si / Al=50 was synthesized and used as a seed in the direct hydrothermal synthesis of a layered zeolite Al-SSZ-70 using the method detailed below. In a typical synthesis of zeolite seeds, 0.0436 g of sodium aluminate (Na2O Al2O3 3H2O) was dissolved in a mixture of 2.89 g of deionized water and 0.128 g of a 50 wt% NaOH aqueous solution. After mixing, 8.70 g of an OSDA solution consisting of 9.7 wt% diisobutylimidazolium hydroxide (DIBI) was added dropwise. After a clear mixture was obtained, 1.14 g of a silica source ( 200g pyrogenic silica) and 0.06g seed (containing Al-SSZ-70 zeolite in calcined form with a Si / Al ratio of 50) and manually stirred. After forming a uniform mixture, the obtained synthetic gel was obtained, which had a composition of 1.0SiO2:0.01Al2O3:0.1NaOH:0.2OSDA:30H2O. The mixed gel was sealed in an autoclave with a 23mL Teflon container and heated at 150°C for 11 days at a speed of 27RPM. After hydrothermal synthesis, the synthesized zeolite powder was recovered by filtration, washed with deionized (DI) water until the measured pH was <8.0, and dried at 80°C overnight. The directly calcined Al-SSZ-70 zeolite product was obtained by calcining the synthesized zeolite at 580°C in air for 5 hours to produce a white powder.
[0062] Example 2
[0063] Synthesis of Layered Al-SSZ-70 Zeolite Using Different Amounts of CTAOH Surfactant
[0064] In the presence of different amounts of surfactant CTAOH solution, hydrothermal synthesis of layered Al-SSZ-70 zeolite. The synthesis process is similar to the synthesis process of Al-SSZ-70 zeolite without surfactant CTAOH as shown above. However, compared with the above-mentioned synthesis without CTAOH, a part of the OSDA is replaced by CTAOH, and the total molar ratio of organic matter / SiO2 (organic matter is composed of OSDA and CTAOH) in the synthetic gel is fixed at 0.2. Therefore, the relative molar ratio of CTAOH to the total organic content changes from 10 mol % to 90 mol %, while keeping the hydroxide concentration constant. The detailed information on the synthetic chemical composition is summarized in Table 4 below.
[0065] In a typical synthesis of layered Al-SSZ-70 of the samples shown in Table 4, 0.0436 g of sodium aluminate (Na2O Al2O33H2O) was dissolved in a mixture of 2.8895 g of deionized water and 0.128 g of a 50 wt% aqueous NaOH solution. After mixing, the required amount of diisobutylimidazolium hydroxide solution (9.7 wt%) and CTAOH solution (10 wt%) were added dropwise. Then, 1.14 g of a silica source ( 200) and 0.06g of seeds (comprising conventional Al-SSZ-70 zeolite seeds in calcined form with Si / Al of 50) and manually stirred. After forming a uniform gel, the resulting synthetic gel was sealed in an autoclave with a 23mL Teflon container and heated at 150°C for 11 days at a speed of 27RPM. After synthesis, the zeolite powder in the synthesized state was recovered by filtration, washed with deionized water until the measured pH <8.0, and dried at 80°C overnight. The obtained dry powder was calcined at 580°C in air for 5 hours to synthesize a calcined form of separated Al-SSZ-70 (x%) zeolite (x represents the molar ratio of CTAOH in the total organic matter used for synthesis).
[0066] Table 4: Synthesis conditions of highly layered Al-SSZ-70 zeolites with different amounts of CTAOH
[0067]
[0068]
[0069] Example 3
[0070] High shear mixing of as-synthesized Al-SSZ-70 zeolite
[0071] As an alternative to direct calcination, as-synthesized materials corresponding to products containing different amounts of CTAOH surfactant (10 mol%, 30 mol%, 50 mol% and 60 mol% CTAOH) were subjected to high shear mixing. This process was performed to produce a greater degree of delamination while avoiding the need for difficult-to-scale sonication, as required in previous syntheses of delaminated zeolites. In a typical process, the as-synthesized zeolite material was made into a wet paste for high shear mixing by mixing about 5 mL of water with 0.5 g of the as-synthesized material and then centrifuging at 8000 RPM for 5 minutes. The supernatant was removed and the remaining wet paste was high shear mixed using a two-phase asymmetric centrifugal mixer (DAC 150.1FVZ SpeedMixer from Flack Tec, Inc.) according to the following process. Typically, 0.75-1.25 g of the wet paste was placed in a 10 g material container with two cylindrical zirconium beads (d = 9.5 mm, l = 10 mm). The resulting mixture was subjected to high shear treatment at 2500RPM for 2 minutes, followed by the addition of 100 μL of deionized water. The mixture was subsequently subjected to high shear mixing again under the same conditions. 10 μL of 1M NH4OH solution was added to the resulting material, and the resulting slurry was subjected to high shear mixing at 1700RPM for 1 minute. The material was then dried overnight at 60°C and calcined at 580°C in air for 5 hours, and the resulting sample was represented as Al-SSZ-70 (x%)-HSM, where x represents the molar ratio of CTAOH in the total organic matter used for synthesis, and HSM represents high shear mixing.
[0072] Example 4
[0073] In situ transmission FTIR pyridine desorption
[0074] The spectral resolution is 2 cm. -1 The transmission Fourier transform infrared (FTIR) spectrum of the self-supporting wafer was recorded using a Nicolet 6700 FTIR spectrometer and 256 scans. The wafer was loaded into an in-situ flow cell (In-situ Research Instruments, Inc., South Bend, IN) and vacuum treated at 523K to dehydrate the sample before pyridine absorption. Background spectra were collected under the same conditions at 323K under vacuum and in the absence of a wafer. Excess pyridine (20mL) was injected into a heated gas manifold (423K) to expose the zeolite wafer in the sample cell for 1 hour at 323K in an Ar stream (50mL / min). Afterwards, at 323K, 423K, 473K, 523K and 573K, in an Ar gas stream (50cm 3Pyridine was desorbed at 100 °C / min and each temperature was kept isothermal for 1 hour. The cell was then re-introduced into vacuum and cooled back to 323 K to obtain the spectrum. -1 The spectrum was normalized using the integrated intensity of the framework Si-O-Si harmonics in the range 1544 cm -1 ν(PyH + ) and 1454cm -1 The L / B ratio was determined by integration of the Lewis and Bronsted bands for ν(PyL) at .
[0075] Example 5
[0076] Catalysis research
[0077] The Friedel-Crafts acylation of 2-methoxynaphthalene (2-MN) using acetic anhydride as acylating agent was used as a probe reaction to determine the catalytic activity of the synthesized H-type Al-SSZ-70 zeolite. This reaction was chosen as a relevant probe because its activity has been previously shown to be representative of the density of external acid sites on an aluminosilicate zeolite. Catalysis was carried out in a Teflon-terminated, 48 mL walled glass reactor equipped with a magnetic stirrer and heated in an oil bath set at 120° C. for 6 hours under autogenous pressure conditions. Before the vessel was introduced into the oil bath, 100 mg of the H-type Al-SSZ-70 zeolite catalyst was charged into the reactor together with 0.987 mmol of 2-methoxynaphthalene and 1.1 mmol of acetic anhydride (10% molar excess of acetic anhydride) in 10 mL of 1,2-dichloroethane solvent. The reaction was placed in an ice bath for 8 minutes after completion. 1.1 mmol of internal standard dodecane was added to the final product just before filtering the solution through a 0.200 μm syringe filter for gas chromatography analysis. The chemicals used in this process were used as received from the manufacturer, and no attempt was made to strictly exclude atmospheric moisture. These conditions were highly deactivating and resulted in extensive coking visible in the catalyst after the reaction, as well as a lack of complete material balance closure.
[0078] The conversion rate of 2-MN is defined as follows:
[0079]
[0080] The yield of the acylated product is defined as follows:
[0081]
[0082] The selectivity of the acylation product is defined as follows:
[0083]
[0084] The initial rates of reaction and formation are defined as follows:
[0085]
[0086]
[0087] As used in this disclosure, the words "comprising" or "including" are intended to serve as open transitional words, which mean that specified elements are included but not necessarily other unspecified elements are excluded. The phrases "consisting essentially of" or "consisting essentially of" are intended to indicate the exclusion of other elements having any substantial meaning to the composition. The phrases "consisting of" or "consisting of" are intended to serve as transitional phrases to indicate that all elements other than the listed elements are excluded, except for only minor trace impurities.
[0088] All patents and publications cited herein are incorporated herein by reference to the extent consistent with this article. It should be understood that some of the above-mentioned structures, functions and operations of the above-mentioned embodiments are not necessary for implementing the present invention, and are included in the description only for the completeness of one or more exemplary embodiments. In addition, it should be understood that the specific structures, functions and operations proposed in the above-mentioned reference patents and publications can be implemented in conjunction with the present invention, but they are not necessary for the implementation of the present invention. Therefore, it should be understood that, in fact, without departing from the spirit and scope of the present invention defined by the appended claims, the present invention can be implemented in other ways other than the specific description.
Claims
1. A method for preparing a layered Al-SSZ-70 zeolite comprising contacting a reaction mixture comprising: (1) Al2O3 source; (2) a silicon dioxide source; (3) imidazolium cation (OSDA); and (4) Hexadecyltrimethylammonium cation (CTA + ).
2. The method of claim 1, wherein the reaction mixture further comprises (5) Al-SSZ-70 zeolite seeds.
3. The method of claim 2, wherein the Al-SSZ-70 zeolite seeds have a Si / Al ratio of at least 50.
4. The method of claim 1, wherein the CTA + The mole % range is the total organic components (OSDA + CTA + ) is 10 mol % to 60 mol %.
5. The method of claim 4, wherein the CTA + The mole % range is from 10 mole % to 50 mole %.
6. The method of claim 4, wherein the CTA + The mole % range is from 30 mole % to 60 mole %.
7. The method of claim 4, wherein the CTA + The mole % range is 50 to 60 mole %.
8. The process of claim 2, wherein a layered Al-SSZ-70 zeolite is recovered having a Si / Al ratio of at least 50.
9. The method of claim 8, wherein the Si / Al ratio is in the range of 50 to 75 mol%.
10. The process of claim 1, wherein the Al-SSZ-70 zeolite is recovered and calcined.
11. The process of claim 1 wherein the Al-SSZ-70 zeolite is recovered and subjected to high shear mixing.
12. The process of claim 11, wherein the Al-SSZ-70 zeolite is recovered from the high shear mixing and calcined.
13. The method of claim 11, wherein the high shear mixing comprises a high shear treatment of at least 1500 RPM for at least 1 minute.
14. The method of claim 13, wherein the high shear mixing comprises a high shear treatment of at least 1500-3000 RPM for a period of time in the range of 1 minute to 30 minutes.
15. The method of claim 11, wherein the high shear mixing comprises a high shear treatment of at least 2500 RPM for at least 2 minutes, followed by a second high shear treatment of at least 1700 RPM for at least 1 minute.
16. The method of claim 1, wherein the imidazolium cation is selected from the group consisting of 1,3-diisopropylimidazolium cation, 1,3-diisobutylimidazolium cation, and 1,3-dicyclohexylimidazolium cation.
17. The method of claim 1, wherein the imidazolium cation is provided in the reaction mixture in the form of a hydroxide.
18. The method of claim 1, wherein the CTA is provided in the reaction mixture in the form of a hydroxide + cation.
19. The process of claim 3 wherein the Al-SSZ-70 zeolite is recovered and subjected to high shear mixing and the product recovered from the high shear mixing is calcined.
20. A layered Al-SSZ-70 product prepared by the method of claim 3.
21. A layered Al-SSZ-70 product prepared by the method of claim 11.
22. The product of claim 21, wherein the product exhibits at least 250 m 2 / g of surface area.
23. The product of claim 21, wherein the product exhibits at least 300 m 2 / g of surface area.
24. The product of claim 21, wherein the product exhibits at least 340 m 2 / g of surface area.
25. The product of claim 21, wherein the product exhibits a 3 / g of micropore volume.